Rosa in Sparkle City - Collins, Poppy (London : Scholastic, 2014)
The fashion fairy princesses are organizing a fairy fashion show! Everything has to be PERFECT and the fairies have fun shopping in Sparkle City to find the best outfits. Drawing on their expert fashion knowledge, they know they are going to pull off the most impressive catwalk extravaganza. The final piece is an amazing silk dress, encrusted with jewels from Jewel Forest. But moments before the show, they discover the stunning dress is ruined! Rosa must use her practical skills - and just a tiny bit of fairy magic - to save the day.
Q
Formerly CIP.
b
b
Keywords: Children's stories